x2+x10=6

To write x2 as a fraction with a common denominator, multiply by 55.

x2⋅55+x10=6

Write each expression with a common denominator of 10, by multiplying each by an appropriate factor of 1.

Multiply x2 and 55.

x⋅52⋅5+x10=6

Multiply 2 by 5.

x⋅510+x10=6

x⋅510+x10=6

Combine the numerators over the common denominator.

x⋅5+x10=6

Simplify the numerator.

Move 5 to the left of x.

5⋅x+x10=6

Add 5x and x.

6×10=6

6×10=6

Cancel the common factor of 6 and 10.

Factor 2 out of 6x.

2(3x)10=6

Cancel the common factors.

Factor 2 out of 10.

2(3x)2(5)=6

Cancel the common factor.

2(3x)2⋅5=6

Rewrite the expression.

3×5=6

3×5=6

3×5=6

3×5=6

Multiply both sides of the equation by 53.

53⋅3×5=53⋅6

Simplify 53⋅3×5.

Cancel the common factor of 5.

Cancel the common factor.

53⋅3×5=53⋅6

Rewrite the expression.

13⋅(3x)=53⋅6

13⋅(3x)=53⋅6

Cancel the common factor of 3.

Factor 3 out of 3x.

13⋅(3(x))=53⋅6

Cancel the common factor.

13⋅(3x)=53⋅6

Rewrite the expression.

x=53⋅6

x=53⋅6

x=53⋅6

Simplify 53⋅6.

Cancel the common factor of 3.

Factor 3 out of 6.

x=53⋅(3(2))

Cancel the common factor.

x=53⋅(3⋅2)

Rewrite the expression.

x=5⋅2

x=5⋅2

Multiply 5 by 2.

x=10

x=10

x=10

Solve for x x/2+x/10=6